Updates for Citrus Nutrient Best Management Practices - Kelly Morgan; Davie Kadyampakeni; Tripti Vashisth (EDIS, 2022)
This article is to review current citrus UF/IFAS fertilizer recommendations and provide updated information on recently approved recommendations on secondary macronutrients and micronutrients. Citrus growers have been very concerned with fertilizer applications and nutrient management since citrus greening (Huanglongbing, HLB) entered Florida.  Lately, citrus growers have become more concerned with nutrient management in the past couple years because of increased inspections and scrutiny of grower adherence to best management practices (BMPs). Unfortunately, HLB has resulted in reduced citrus yields the past 17 years and no cure has been developed but nutrient management appears to be one key tool box for maintaining tree production until that silver bullet is found. The UF/IFAS committee that approves fertilizer recommendations recently approved the increase of micronutrient and secondary macronutrients based on research results. These improved and revised recommendations will appear in the 2023 Citrus Production Guide.  Currently research on fertilizer application rates of N and P are continuing with the goal of improving UF/IFAS recommendations for HLB-affected trees.